The association between dietary omega-3 intake and osteoporosis: a NHANES cross-sectional study - Liu, Zhiwen; Cai, Shaoming; Chen, Yuzhen; Peng, Zijing; Jian, Huanling; Zhang, Zhihai; Huang, Hongxing (Frontiers in Nutrition, 2025)
Recent research suggests that omega-3 fatty acids may play a role in bone metabolism through their influence on bone mineral density (BMD) and the regulation of bone turnover markers. However, epidemiological evidence linking omega-3 intake to the risk of developing osteoporosis is still emerging and remains inconclusive. This study aims to clarify the role of dietary omega-3 fatty acids in the prevention of osteoporosis.We analyzed data from 8,889 participants categorized into normal, osteopenia, and osteoporosis groups based on their BMD scores from the National Health and Nutrition Examination Survey (NHANES). We measured dietary omega-3 intake using two 24-hour dietary recall interviews. Dietary omega-3 intake was quantified and divided into quartiles. Multivariate logistic regression and subgroup analysis were used to explore the correlation between dietary omega-3 intake and osteoporosis. The dose-response relationship between the two was analyzed with a restricted cubic spline (RCS).Higher dietary intake of omega-3 fatty acids was inversely associated with the risk of osteoporosis. Participants in the highest quartile of omega-3 intake had a significantly lower risk (OR = 0.71, 95% CI: 0.53-0.93) compared to those in the lowest quartile, with a consistent trend across all adjusted models (p for trend < 0.05). Subgroup analyses indicated stronger associations in individuals under 60 years of age, female and non-smokers. In individuals aged under 60, higher omega-3 intake was associated with significantly reduced osteoporosis risk (OR = 0.51, 95%CI:0.26-0.95), females showed a protective effect of high omega-3 intake against osteoporosis (OR = 0.65, 95% CI: 0.49-0.87). Among non-smokers, higher omega-3 intake was associated with a lower risk of osteoporosis (OR = 0.64, 95% CI:0.45-0.90), whereas in smokers, the association was not evident (OR =0.91, 95%CI:0.55-1.52). No significant associations were found in older participants or smokers. Intake of omega-3 and osteoporosis were linearly related (P for nonlinear = 0.366).This study demonstrates a significant inverse relationship between dietary omega-3 fatty acid intake and osteoporosis risk, suggesting omega-3s play a crucial role in bone health. However, further longitudinal studies are needed to confirm these findings and refine dietary recommendations for osteoporosis prevention.